Camera stabilizer - Tuan Ibrahim, Tuan Mohd Hafeez; Ismail, Suhairi; Basharie, Siti Mariam; Abdul Rahman, Muhammad Qusyairi; Ahmad, Muhammad Shukri; Soo, Jun Chun; Osman, Muhammad Nur Fikri; Baskaran, Simresan (Penerbit UTHM, 2020)
In the world of videography and cinematography, visible camera shake is a common thing. Visible camera shake usually is caused by the movement of the camera operator when using a camera. Camera stabilizer is a device used by many people to reduce or remove the visible camera shake to create better quality videos. Most camera stabilizers available in the global market uses advanced technologies that can stabilize a camera very easily. However, the use of advance technologies has caused a spike in the price of these camera stabilizers. There are very little to none option when it comes to a low-cost camera stabilizer available in the market. This project main purpose is to design and fabricate a low-cost camera stabilizer that would be affordable to more people from different walk of life. The low-cost camera stabilizer will use simple mechanism to stabilize a camera instead of advance technologies that are used on most high cost camera stabilizers. The result shows that this low-cost camera stabilizers were able to stabilize a camera and reduce the visible camera shake using the balancing mechanism.